2022
DOI: 10.1371/journal.pone.0268757
|View full text |Cite
|
Sign up to set email alerts
|

Random forest vs. logistic regression: Predicting angiographic in-stent restenosis after second-generation drug-eluting stent implantation

Abstract: As the rate of percutaneous coronary intervention increases, in-stent restenosis (ISR) has become a burden. Random forest (RF) could be superior to logistic regression (LR) for predicting ISR due to its robustness. We developed an RF model and compared its performance with the LR one for predicting ISR. We retrospectively included 1501 patients (age: 64.0 ± 10.3; male: 76.7%; ISR events: 279) who underwent coronary angiography at 9 to 18 months after implantation of 2nd generation drug-eluting stents. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Lastly, our study in premature AMI patients identified metabolic variables, including DM, elevated LDLC, SBP, and BMI, as independent predictors of ISR, thus supporting and expanding upon existing research findings. While some studies indicated that metabolic syndrome did not heighten ISR risk, others have provided evidence that specific metabolic indicators independently forecasted ISR risk [ 24 , 33 , 34 ]. Restenosis progression commenced shortly after the intervention, with ISR arising from endothelial damage caused by PCI and subsequent neointimal and vascular smooth muscle cell (VSMC) proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, our study in premature AMI patients identified metabolic variables, including DM, elevated LDLC, SBP, and BMI, as independent predictors of ISR, thus supporting and expanding upon existing research findings. While some studies indicated that metabolic syndrome did not heighten ISR risk, others have provided evidence that specific metabolic indicators independently forecasted ISR risk [ 24 , 33 , 34 ]. Restenosis progression commenced shortly after the intervention, with ISR arising from endothelial damage caused by PCI and subsequent neointimal and vascular smooth muscle cell (VSMC) proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when combined, the CKM score achieved an AUC-ROC of 0.834, outperforming other established ISR risk prediction models [ 4 , 6 , 9 ]. Furthermore, the predictive power of the CKM score was externally validated in an independent cohort, which is a rarity in most models [ 5 , 24 , 34 ]. In light of these findings, the newly proposed CKM score holds three practical implications for the assessment and management of patients with premature AMI.…”
Section: Discussionmentioning
confidence: 99%